2012
DOI: 10.1063/1.4768472
|View full text |Cite
|
Sign up to set email alerts
|

Influence of surface tension on cavitation noise spectra and particle removal efficiency in high frequency ultrasound fields

Abstract: Influence of surface tension on cavitation noise spectra and particle removal efficiency in high frequency ultrasound fields, Journal of Applied Physics, 112(11). Archived versionFinal publisher's version / pdf Influence of surface tension on cavitation noise spectra and particle removal efficiency in high frequency ultrasound fields Physical cleaning methods are applied in the semiconductor industry and have become increasingly challenging due to the continued scaling of semiconductors device elements. Cavita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…These results suggest that increasing the initial concentration of detergent leads to a decrease in the inception pressure, the reason for which can be the change in the water tensile strength after mixing with detergent. The obtained results are consistent with previous findings, which show that surfactants (the primary component in detergents) facilitate bubble growth and in consequence inception by influencing surface tension, interfacial resistance to mass transfer, and surface rheological properties. , Thus, it can be inferred that the increase in the liquid detergent-to-water ratio leads to cavitation inception in smaller upstream pressures.…”
Section: Resultssupporting
confidence: 92%
“…These results suggest that increasing the initial concentration of detergent leads to a decrease in the inception pressure, the reason for which can be the change in the water tensile strength after mixing with detergent. The obtained results are consistent with previous findings, which show that surfactants (the primary component in detergents) facilitate bubble growth and in consequence inception by influencing surface tension, interfacial resistance to mass transfer, and surface rheological properties. , Thus, it can be inferred that the increase in the liquid detergent-to-water ratio leads to cavitation inception in smaller upstream pressures.…”
Section: Resultssupporting
confidence: 92%
“…To best gain insight into potential mechanisms of DCM-dependent toxicity, we compared the characteristics of DCM, EtAc, and TCM. Solvents with higher vapor pressure and lower surface tension undergo vapor bubble formation and subsequent cavitation at less extreme pressures [41,42]. Because DCM has the highest vapor pressure of the three solvents as calculated from the Antoine equation (DCM: 353 mmHg, TCM 158 mmHg, EtAc 74 mmHg at 20°C) [43], we speculate that under the nanoparticle formulation parameters used in our experiments, the sonication energy input was mild enough that cavitation only occurred with DCM as the organic solvent.…”
Section: Exploration Of Peg Degradation and Toxic Product Formationmentioning
confidence: 91%
“…Camerotto et al [ 17 ] conducted a study on the effects of lower bulk surface tension on bubble activity and surface cleaning performance. It was demonstrated that cavitation activity, measured by means of ultra-harmonic cavitation noise, is enhanced in the presence of lower surface tension.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the liquid surface tension not only affected the bubble’s stability in the ultrasonic field but also obviously influenced the characteristics of the bubble’s typical motions near a rigid wall, such as moving, collapse, and rebound. In addition, more researchers were more willing to analyze the influence of liquid surface tension with various numerical methods [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Among these methods, the R–P equation (Rayleigh–Plesset equation) is regarded as the most classic one [ 28 ].…”
Section: Introductionmentioning
confidence: 99%